High rates of depression anxiety and suicidal ideation among inpatients in general hospital in China. (3rd April 2019) - Huang, Mingjin; Liu, Yang; Wang, Jian; Mo, Liling; Wang, Yu; Chen, Liang; Dong, Zaiquan; Guo, Wanjun; He, Ning; Chen, Ran; Luo, Shanxia; Yu, Jianying; et al.
Abstract: Objective: To investigate the prevalence rates of depression anxiety and suicidal ideation among Chinese general hospital inpatients and to identify the potential associations with sociodemographics. Method: A cross-sectional survey was applied in a Chinese general hospital. A questionnaire set, including sociodemographic variables, Patient Health Questionnaire-9 (PHQ-9), and the Generalized Anxiety Disorder Scale-7 (GAD-7), was completed by the participants. Clinically significant depression (CSD) and clinically significant anxiety (CSA) were defined as a score above 10 on the two scales. CSD and CSA are proxy measures but not specific diagnoses of mental disorders. Results: Data from 1329 patients were included in the final analysis. 422 (31.8%) reported clinically significant depressive symptoms, 83 (6.3%) reported frequent suicidal ideation, and 204 (15.3%) reported clinically significant anxiety. Household income was negatively associated with CSD. Inpatients with lower household incomes and educational levels had higher rates of CSA. Middle-aged inpatients were more prone to suicidal ideation, and stable marital status was related to less suicidal ideation. Conclusion: Depression, anxiety, and suicidal ideation were determined to be common psychological problems in Chinese inpatients. Chinese medical personnel must pay attention to the mental health conditions of inpatients, particularly inpatients with lower income, educational levels, and poor marital status. Key Points: This is one of the first studies focusing on the prevalence of depression and anxiety in Chinese hospitalized inpatients in non-psychiatric departments of a general hospital. The PHQ-9 and GAD-7 were determined to be potential screening tools to aid Chinese medical workers in recognizing depression and anxiety in nonpsychiatric departments. The prevalence of depression, anxiety and suicidal ideation was observed to be relatively high in inpatients, which requires more attention from Chinese clinicians.